BUSINESS RISK COVERAGE IN PRINTING AND GRAPHIC PRE ORDER TRANSACTIONS: An analysis of Ijarah 'Ala Al-'Amal Theory - Mawadatul Ula; Muhammad Syuib; Hajarul Akbar (JURISTA: Jurnal Hukum dan Keadilan, 2022)
Warna Graphic Design Company is a company engaged in printing and graphics. This service company operates by implementing a pre order system, named order first, receive benefits later. Where in fiqh muamalah using ijarah 'ala al 'amal (rent or wages). Each company must have its own risks, both from within and from outside the company. The risks that occur in the Graphic Design Color company come from outside the company. Musta'jir (consumers) who use the company's services make defaults to the company and do not fulfill their obligations. This causes the company to suffer heavy losses because it does not receive its rights/wages as it should. The research questions in this case are how the implementation system of pre order transactions in printing and graphic business at Warna Graphic Design, how the form of risk coverage in printing and graphic business at Warna Graphic Design, and how the analysis of business risk coverage on pre order transactions in printing and graphic business at Warna Graphic Design according to ijarah 'ala al 'amal. This research uses qualitative methods with descriptive analysis. Data comes from primary data obtained in the field and secondary data obtained from literature research. The results of the study found that mu'jir until now continues to try to collect debts to musta'jir in good ways (ahsan) according to Islamic law. Mu'jir has taken the right steps according with the ijarah 'ala al 'amal contract. Even though the company has lost money because the musta'jir has defaulted, the company still fulfills its obligations to the third parties as raw material providers as it should.